2011
DOI: 10.1002/ejic.201100488
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Stable Triple Helicates of Quaterimidazole: Three‐Dimensional Crystal Structures and Optical Resolution by Chiral‐Column HPLC

Abstract: Complex formation of quaterimidazole with FeII, CoII, and NiII yielded dinuclear triple helicates in the solution state by the self‐assembling ability of the ligand based on the strong chelating coordination bonds. Crystallization of the CoII complex from aqueous solution afforded the CoIII complex with a triple‐helical structure. X‐ray crystal structure analyses revealed that the helicates are linked through N–H···X hydrogen bonds with counteranions and solvent molecules to form three‐dimensional networks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…A general strategy to influence the stereochemistry of self-assembled systems and capsules ,, is the introduction of additional stereocenters, in the form of either enantiopure building blocks, ,,,− chiral ancillary ligands, ,, chiral guests, , or counterions. , The fixed stereochemistry of these stereocenters thus influences the conformations of new stereocenters formed during self-assembly resulting in diastereomerically enriched structures. The isolation of enantiomerically pure assemblies has been achieved through self-resolution or chiral chromatography of assemblies originally prepared in racemic form, , as pioneered in the context of Ga 4 L 6 clusters by the Raymond group . Systems with stereochemical memory ,, are able to process and conserve the information first introduced by a chiral auxiliary after its removal or replacementthe crucial step of this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…A general strategy to influence the stereochemistry of self-assembled systems and capsules ,, is the introduction of additional stereocenters, in the form of either enantiopure building blocks, ,,,− chiral ancillary ligands, ,, chiral guests, , or counterions. , The fixed stereochemistry of these stereocenters thus influences the conformations of new stereocenters formed during self-assembly resulting in diastereomerically enriched structures. The isolation of enantiomerically pure assemblies has been achieved through self-resolution or chiral chromatography of assemblies originally prepared in racemic form, , as pioneered in the context of Ga 4 L 6 clusters by the Raymond group . Systems with stereochemical memory ,, are able to process and conserve the information first introduced by a chiral auxiliary after its removal or replacementthe crucial step of this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…76,77 In contrast, the chiral memory concept®first reported by Aida 78 and Yashima 79 and applied to porphyrin aggregates and helical polymers, respectively®has allowed for the enantioselective synthesis of several self-assembled structures.…”
Section: Stereochemical Memory Effectmentioning
confidence: 99%
“…The structural features of 4,4′‐Bim has resulted in the construction of diverse and multidimensional H‐bonding networks in transition‐metal complexes17 and CT salts with TCNQ 18. Furthermore, our intensive studies on the self‐assembly of oligo(imidazole)s revealed that their rigid molecular structures and robust chelating coordination bonds formed triple helicates with various d‐block transition‐metal ions exhibiting high selectivity and inertness 19c,19d. These features of oligo(imidazole)–helicates allowed the design of the first electron‐spin‐based Lloyd model for scalable matter spin‐qubit 19c,20…”
Section: Introductionmentioning
confidence: 99%